Comparing effects of beetroot juice and Mediterranean diet on liver enzymes and sonographic appearance in patients with non-alcoholic fatty liver disease: a randomized control trials - Fateh, Hawal Lateef; Rashid, Sameeah Abdulrahman; Muhammad, Sarmad S.; Al-Jaf, Sabah H.; Ali, Ayad M. (Frontiers in Nutrition, 2023)
In both developed and developing countries, non-alcoholic fatty liver disease (NAFLD) has lately risen to the top of the list of chronic liver illnesses. Although there is no permanent cure, early management, diagnosis, and treatment might lessen its effects. The purpose of conducting the current study is to compare the effects of beetroot juice and the Mediterranean diet on the lipid profile, level of liver enzymes, and liver sonography in patients with NAFLD.In this randomized controlled trial, 180 people with a mean age of (45.19±14.94) years participated. Participants ranged in age from 19 to 73. The mean weight before intervention was (82.46±5.97) kg, while the mean weight after intervention was roughly (77.88±6.26) kg. The trial lasted for 12 weeks. The participants were split into four groups: control, a Mediterranean diet with beet juice (BJ+MeD), Mediterranean diet alone (MeD), and beetroot juice (BJ). The Mediterranean diet included fruits, vegetables, fish, poultry, and other lean meats (without skin), sources of omega-3 fatty acids, nuts, and legumes. Beetroot juice had 250 mg of beetroot. Data analysis was done using SPSS software (version 26.0). P <0.05 is the statistical significance level.Results: Following the intervention, Serum Bilirubin, alkaline phosphatase (ALP), alanine transaminase (ALT), serum cholesterol (CHOL), triglyceride (TG), and low-density lipoprotein (LDL) levels were significantly decreased in the BJ+MeD, BJ, and MeD groups (P = 0.001). Also, high-density lipoprotein (HDL) significantly increased in the BJ+MeD, BJ, and MeD groups (P = 0.001), while decreasing in the Control group (P = 0.001).The research findings indicate a significant reduction in hepatic steatosis among the groups receiving beetroot juice (BJ) and beetroot juice combined with the Mediterranean diet (BJ+MeD). This suggests that beetroot juice holds potential as an effective treatment for nonalcoholic fatty liver disease (NAFLD) in adults. Furthermore, the combination of beetroot juice with the Mediterranean diet showed enhanced efficacy in addressing NAFLD.